Dehydrogenation characteristics of ammonia borane via boron-based catalysts (Co-B, Ni-B, Cu-B) under different hydrolysis conditions - Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In the present study, dehydrogenation characteristics of ammonia borane (NH3BH3) catalyzed via boron-based catalysts under different hydrolysis conditions were investigated. A series of boron-based catalysts (Co1-x-B-x, Ni1-x-B-x, and Cu1-x-B-x, x: 0.25, 0.50, 0.75) were prepared by so gel method. Gels were calcinated at different temperatures (250 degrees C, 350 degrees C, and 450 degrees C) in order to obtain the boron-based catalysts. XRD characterizations revealed that Co-B, Ni-B, and Cu-B crystalline structures were formed during calcination at 450 degrees C. Hydrogen generation measurements were performed in order to determine the optimum composition of the boron-based catalyst. The maximum hydrogen generation rates were 7607 ml min(-1) gcat(-1), 3869 ml min-1 gcat-1 and 1178 ml min(-1) gcat(-1) for CO0.75B0.25, Ni0.75B0.25 and Cu0.75B0.25, respectively. Furthermore, the hydrolysis of NH3BH3 was performed at 20 degrees C, 40 degrees C, 60 degrees C and 80 degrees C under magnetic stirring (750 rpm), ultrasonic irradiation and non-stirring in order to determine how these parameters effect hydrolysis. Activation energies (E-a) were calculated by evaluation of the kinetic data. Under ultrasonic irradiation, the E-a in. the presence of CO0.75B0.25, Ni0.75B0.25 and Cu0.75B0.25 were 40.85 kJ mol(-1), 43.19 kJ mol(-1) and 48.74 kJ mol(-1), respectively, which compares favorably with results reported in the literature. Thus, the catalytic activities of the boron-based catalysts were found to be Cu < Ni < Co and the best reaction condition for the catalytic hydrolysis of NH3BH3 was determined to be non-stirring < magnetic stirring < ultrasonic irradiation. Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Ammonia borane; Hydrolysis; Boron catalyst; Non-stirring; Magnetic stirring; Ultrasonic irradiation; CHEMICAL HYDROGEN STORAGE; AMINE-BORANE; GENERATION; DECOMPOSITION; Chemistry; Electrochemistry; Energy & Fuels